Plato on God as nous - Menn, Stephen Philip, 1964- (Journal of the history of philosophy monograph series., 1995)
This book is the first sustained modern investigation of Platoʹs theology. A central thesis of the book is that Plato had a theology -- not just a mythology for the ideal city, not just the theory of forms or the theory of cosmic souls, but also, irreducible to any of these, an account of God as Nous (Reason), the source of rational order both to souls and the world of bodies. The understanding of God as Reason, and of the world as governed directly or indirectly by Reason, is worked out in the dialogues of Platoʹs last period, the Statesman, Philebus, Timaeus, and Laws. These dialogues offer a strategy for explaining the physical world that goes beyond anything in the middle dialogues, and gives the best starting point for understanding the cosmologies and theologies of Aristotle, the Stoics, and later ancient thinkers. -- Back cover.